The King James only controversy - White, James R. (James Robert), 1962- (Minneapolis, Minn. : Bethany House, 2009)
"A thoroughly researched discussion of the development of Bible translations ancient and modern, including key differences between versions such as the New International, New American Standard Bible, and the Authorized Version of 1611"--Provided by publisher.
The King James only controversy -- King James only -- "If it ain't broke-- " -- Starting at the beginning -- Putting it together -- The King James only camp -- Translational differences -- Textual differences -- The Son of God, the Lord of Glory -- Problems in the KJV -- Questions and answers -- Let the reader understand-- -- The textual data.
Includes bibliographical references (p. 341-350) and indexes.
Keywords: Bible. -- Versions -- Authorized; Bible. -- Versions; Bible -- Criticism, Textual